Math, asked by varshakolli7026, 1 year ago

Solve the using suitable properties
(a) 8326429*(-98)+(-8326429)*(-2)
(b) (-7624928)*997+(7624928)*(-3)
(c) (-98)*(-9)+98. (d) (-237)*(-99)+237
(e) (-563)*(-999)+563 (f) 253*(100-1)
(g) 567*(100-1) (h) (-34)*1002
(I) (-67)*101. (j) (-84)*99

Answers

Answered by beenarawat4
8

Step-by-step explanation:

8326429*(-98)+(8326429)*(-2)

Answered by smithasijotsl
0

Answer:

Step-by-step explanation:

Recall the properties

The distributive property of multiplication over the addition of integers is given by

If a,b,c are any three integers, then

a(b+c) = a×b +a×c

(a) 8326429×(-98)+(-8326429)×(-2)

Applying distributive property we get

a = 8326429, b = -98 and c = -2

8326429×(-98)+(-8326429)×(-2)

= 8326429((-98)+(-2))

= 8326429 × -100

= -832642900

8326429×(-98)+(-8326429)×(-2) =  -832642900

b) (-7624928)×997+(7624928)*(-3)

Applying distributive property we get

a = 7624928, b = -997 and c = -3

= 7624928×(-997)+(7624928)×(-3)

=  7624928((-997)+(-3))

=  7624928× -1000

= -7624928000

(-7624928)×997+(7624928)*(-3) = -7624928000

c) (-98)×(-9)+98.

(-98)×(-9)+98.1 = (98)×(9)+98.1

Applying distributive property we get

a= 98, b = 9 and c = 1

(98)×(9)+98.1 = 98(9+1)

= 98×10

= 980

(-98)×(-9)+98 = 980

d) (-237)×(-99)+237

(-237)×(-99)+237 = (237)×(99)+237×(1)

Applying distributive property

a = 237, b = 99 and c = 1

(237)×(99)+237×(1) = 237(99+1)

= 237 × 100

= 23700

(-237)×(-99)+237 = 23700

e)  (-563)×(-999)+563

(-563)×(-999)+563 = 563×999+563×1

Applying distributive property

a = 563, b = 999 and c= 1

= 563(999+1)

= 563 ×1000

= 563000

(-563)×(-999)+563 =  563000

f) 253×(100-1) = 253×(100+(-1))

Applying distributive property

a = 253, b = 100 and c = -1

= 253×(100+(-1)) = 253×100 + 253×(-1)

=  25300 - 253

= 25047

253×(100-1) = 25047

g) 567×(100-1) = 567×(100+(-1)

Applying distributive property

a = 567, b = 100 and c = -1

= 567×(100+(-1)) = 567×100 + 567×(-1)

=  56700 - 567

= 56133

567×(100-1) =  56133

h) (-34)×1002 = (-34) ( 1000 +2)

Applying distributive property

a = (-34) , b = 1000 and c = 2

= (-34) × 1000+ (-34) × 2

= -34000 -68

= - 34068

(-34)×1002 = - 34068

i) (-67)×101 = (-67)(100+1)

Applying distributive property

a = (-67) , b = 100 and c = 1

= (-67×100) + (-67×1)

= -6700 - 67

= -6767

(-67)×101 = -6767

j)(-84)×99 = (-84)(100 + (-1))

Applying distributive property

a = (-84) , b = 100 and c = -1

(-84)(100 + (-1)) = (-84)×100 + (-84)×(-1))

= -8400 + 84

= -8316

(-84)×99 = -8316

#SPJ2

Similar questions